2022
DOI: 10.1002/mco2.151
|View full text |Cite
|
Sign up to set email alerts
|

The SARS‐CoV‐2 main protease (Mpro): Structure, function, and emerging therapies for COVID‐19

Abstract: The main proteases (Mpro), also termed 3‐chymotrypsin‐like proteases (3CLpro), are a class of highly conserved cysteine hydrolases in β‐coronaviruses. Increasing evidence has demonstrated that 3CLpros play an indispensable role in viral replication and have been recognized as key targets for preventing and treating coronavirus‐caused infectious diseases, including COVID‐19. This review is focused on the structural features and biological function of the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(108 citation statements)
references
References 340 publications
1
79
0
Order By: Relevance
“…The potential applications of the zoliniums and their derivatives in drug discovery were demonstrated via targeting the SARS-CoV-2 3CL protease, an essential enzyme for virus replication in host cells. , It was found that 5B could inhibit SARS-CoV-2 3CL pro in a dose- and time-dependent manner, with an IC 50 value as low as 3.66 μM following a long preincubation time (60 min). By contrast, the IC 50 value of 5B against 3CL pro was 75.01 μM without a long preincubation time (Figure e and Figure S7).…”
Section: Resultsmentioning
confidence: 99%
“…The potential applications of the zoliniums and their derivatives in drug discovery were demonstrated via targeting the SARS-CoV-2 3CL protease, an essential enzyme for virus replication in host cells. , It was found that 5B could inhibit SARS-CoV-2 3CL pro in a dose- and time-dependent manner, with an IC 50 value as low as 3.66 μM following a long preincubation time (60 min). By contrast, the IC 50 value of 5B against 3CL pro was 75.01 μM without a long preincubation time (Figure e and Figure S7).…”
Section: Resultsmentioning
confidence: 99%
“…Each monomer contains three domains. More in detail, domain I (residues 8–101) and domain II (102–184) fold in an antiparallel β-barrel -where the active site with the Cys145-His41 catalytic dyad is located [ 7 ] whereas domain III (residues 201–306) is involved in the process of dimerization that is critical for the function of the enzyme [ 8 ]. The two subunits of M pro bind to each other via the N-terminus (residues 1–7) where the Ser1 of each monomer completes and stabilizes the S1 substrate binding pocket of the adjacent monomer [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…These are summarized in Table 2 . Some clinical advances in the development of small-molecule drugs targeting SARS-CoV-2 3CL pro have been reported by Hu et al [ 91 ]. The noncovalent, reversible oral nonpeptidic SARS-CoV-2 3CL protease inhibitor clinical candidate, namely S-217622 developed by Shionogi, has been deeply studied [ 92 ].…”
Section: Recent Studies For New Drugsmentioning
confidence: 99%